2021
DOI: 10.5507/bp.2020.023
|View full text |Cite
|
Sign up to set email alerts
|

The use of platelet-rich fibrin in the surgical treatment of medication-related osteonecrosis of the jaw: 40 patients prospective study

Abstract: Objectives. Medication-related osteonecrosis of the jaw (MRONJ) is defined as exposed bone in the maxillofacial region persisting for more than eight weeks in patients who are or were treated with antire sorptive or antiangiogenic agents and had no radiation therapy to the craniofacial region or obvious metastatic disease of the jaws. It is a recognised side effect of antiresorptive or antiangiogenic medication. To date, there is no specific gold standard treatment for MRONJ cases. The aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…It was reported that healing was not present in only 6 patients, and no healing was observed in 4 of these patients due to the lack of possibility of completely removing the necrotic bone. 39 Maluf et al 23 stated that healing could be observed in 2 patients with stage II MRONJ after L-PRF application with bone debridement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that healing was not present in only 6 patients, and no healing was observed in 4 of these patients due to the lack of possibility of completely removing the necrotic bone. 39 Maluf et al 23 stated that healing could be observed in 2 patients with stage II MRONJ after L-PRF application with bone debridement.…”
Section: Resultsmentioning
confidence: 99%
“…Zelinka and colleagues observed that the success rate was 85% in 40 patients with MRONJ to whom PRF was applied after resection, although 85% of these patients were using high-dose antiresorptive drugs for malignant diseases. It was reported that healing was not present in only 6 patients, and no healing was observed in 4 of these patients due to the lack of possibility of completely removing the necrotic bone 39. Maluf et al23 stated that healing could be observed in 2 patients with stage II MRONJ after L-PRF application with bone debridement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To illuminate the effect of PRF used at surgical interventions for the treatment of osteonecrosis of the jaw, six of thirteen studies were reviewed in detail [ 73 , 74 , 75 , 76 , 77 , 78 ]. Four studies compared surgical treatment with additional use of PRF and conventional treatment [ 73 , 74 , 75 , 78 ]. Three studies observed management of preexisting MRONJ using PRF [ 74 , 75 , 77 ].…”
Section: Main Textmentioning
confidence: 99%
“…Low-risk patients were treated with sutures and LLLT, stage 0 patients took antibiotics, sutures, and LLLT, stage 1–3 patients received a perioperative antibiosis and were treated with piezo-surgery and additional LLLT and PRF were applied at the wound. The study concluded a high rate of success in all groups and a total healing rate of 91.66% in the third group using PRF [ 73 ]. Two studies investigated the possible prevention of MRONJ followed by oral surgeries in patients at risk [ 76 , 78 ].…”
Section: Main Textmentioning
confidence: 99%